Model Testing Whistleblowing: Does Materiality Level Matter? - Caesar Marga Putri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to empirically test the effectiveness of the whistleblowing model in encouraging individuals to report wrongdoing. Based on path-goal theory, leaders will help and support their employees in achieving their goals and ensure that these goals align with organizational goals. Therefore, an individual's intention to report fraud will be greater if there is a clear structure for achieving goals and reducing obstacles. The individual's need for security, as expressed in Maslow's hierarchy theory, requires an anonymous reporting channel. This study was tested using an experimental method involving 58 participants from two universities. The results showed that under structural model conditions, both anonymous and non-anonymous channels were equally effective in encouraging individuals to whistleblow. Between the two channels, there was no difference in the intention to report fraud. In addition, this study also tested the influence of the materiality level of fraud, material and immaterial, the results showed that the materiality level also had no difference in reporting both anonymously and non-anonymously.